2020
DOI: 10.1101/2020.10.02.323980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The TRIM9/TRIM67 neuronal interactome reveals novel activators of morphogenesis

Abstract: TRIM9 and TRIM67 are neuronally-enriched E3 ubiquitin ligases essential for appropriate morphogenesis of cortical and hippocampal neurons and fidelitous responses to the axon guidance cue netrin-1. Deletion of murine Trim9 or Trim67 results in neuroanatomical defects and striking behavioral deficits, particularly in spatial learning and memory. TRIM9 and TRIM67 interact with cytoskeletal and exocytic proteins, but the full interactome is not known. Here we performed the unbiased proximity-dependent biotin iden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 105 publications
1
10
0
Order By: Relevance
“…However, simulations in Trim9 −/− neurons overestimated expansion, suggesting possibly that endocytosis was also elevated in these neurons. Consistent with this idea, we recently identified several candidate TRIM9 interactors associated with clathrin coats ( Menon et al, 2020 ). We conclude that VAMP2-mediated fusion is the primary source of membrane addition in developing neurons and that manipulating exocytic frequency or mode alters neuronal growth.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…However, simulations in Trim9 −/− neurons overestimated expansion, suggesting possibly that endocytosis was also elevated in these neurons. Consistent with this idea, we recently identified several candidate TRIM9 interactors associated with clathrin coats ( Menon et al, 2020 ). We conclude that VAMP2-mediated fusion is the primary source of membrane addition in developing neurons and that manipulating exocytic frequency or mode alters neuronal growth.…”
Section: Discussionsupporting
confidence: 54%
“…Because few interaction partners of TRIM67 are known, we used the BioID method ( Roux et al, 2012 ) to identify candidate TRIM67-interacting partners that may regulate exocytosis ( Menon et al, 2020 ). One interesting candidate and the only SNARE protein significantly enriched (~4-fold) over the negative control (Myc-BirA*; Table S1 ) was SNAP47, a t-SNARE in the SNAP25 family.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we identified a putative TRIM9 and TRIM67 interactome using proximitydependent labeling with the promiscuous biotin ligase (BirA*) attached to either TRIM9 or TRIM67 (Menon et al, 2020). A comparison of the ubiquitylated proteome from developing brains with the top 0.25% of the interaction candidates identified peptides from 55 proteins that showed an increase or decrease (albeit insignificant) in ubiquitylation levels in the absence of Trim9, Trim67 , or both relative to wildtype (Figure 1B-D).…”
Section: Resultsmentioning
confidence: 99%